Prognostic factors for conversion to generalization in ocular myasthenia gravis. Issue 19 (14th May 2021) - Witthayaweerasak, Juthamat; Rattanalert, Narisa; Aui-aree, Nipat
Abstract : Abstract: Patients with ocular myasthenia gravis (OMG) are frequently treated to prevent the development of generalized myasthenia gravis (GMG). This retrospective cohort study aimed to assess prognostic factors associated with conversion to GMG. We analyzed the time from the onset of OMG symptoms to GMG in relation to demographic variables, clinical findings, initial investigation results, and treatment regimens using Kaplan–Meier survival curves and multivariate Cox proportional regression analysis. Of 115 patients diagnosed with OMG (median follow-up time, 2.9 years), 28 (30.4%) developed GMG. The 2-year probability of GMG conversion was 23.7%. Patients with thymic abnormalities and a positive response to repetitive facial nerve stimulation had a significantly higher risk than those with negative results (hazard ratios [HR] 4.28, P  < .001 and HR 3.84, P  = .04, respectively). Treatment with immunosuppressants was found to be a preventive factor for secondary generalization (HR 0.36, P  = .02). Patients with OMG had a low risk of developing GMG. Immunosuppressive treatments may mitigate disease progression. Chest imaging and repetitive nerve stimulation should be routinely performed to assess the risk of generalization.